Hubungan antara Dimensi Fungsionalitas Keluarga dan Subjective Well-Being (SWB) pada Ibu yang Memiliki Anak Disabilitas Intelektual di SLB – C Bandung - Arfa Tiara Shafanisa; Endeh Azizah; Evi Ema Victoria (Humanitas (Jurnal Psikologi), 2017)
This study was conducted to discover the correlation between family functioning and Subjective Well-Being (SWB) toward mothers who have an intellectual disability child at SLB – C Bandung, total respondent are 52 persons. The tool to measure family functioning is Family Assessment Device (Epstein, Bishop, & Levin 1978), which was translated by Triad English Centre and modified by the researcher. The tool to measure SWB was created by researcher, which was based on theory by Diener (2008). Each total score dimension family functioning being correlated with total score SWB using pearson correlation test on SPSS program for windows. The statistic result shows there are two dimension which have significantly positive correlation with SWB, namely problem solving (r = 0,293), and communication (r = 0,385), whereas roles, affective responsiveness, affective involvement, and behavior control are not significantly related with SWB (each coefficient r = 0,092, r = 0,180, r = 0,105, and r = 0,082). Conclusion from this study are from six dimension of family functioning, there are  two dimension which have a significant positive correlation with SWB, both of them are problem solving and communication. However, four dimension of family functioning are not related with SWB. The researcher suggest a further correlational study on family functioning and SWB with using one SLB - C. Other than that, the researcher suggest to mothers whom have an intellectual disability child at SLB – C Bandung to join a productive activity to increase SWB. Keywords:  Family functioning, Subjective Well-Being (SWB)